Editorial Commentary: An Optimal Classification System to Guide Prognosis and Treatment in Greater Trochanteric Pain Syndrome: Now We're Speaking the Same Language - Harris, Joshua D (Arthroscopy, 2021)
The optimal classification system in arthroscopic and related surgery research and clinical practice should be clinically relevant, descriptive, reproducible, simple, inexpensive, safe, and widely applicable. For the hip, classification systems that characterize intra-articular disorders like femoroacetabular impingement (FAI) syndrome, dysplasia, labral tears, and articular cartilage disease predominate the literature. Recently, awareness of peritrochanteric and other extra-articular disorders has increasingly led to greater recognition, diagnosis, and treatment of what has been historically known as "just bursitis". These disorders are far more complex and include greater trochanteric pain syndrome, the spectrum of gluteal tendon pathology, greater trochanteric bursitis, snapping iliotibial band (external coxa saltans), and greater trochanteric-ischial impingement. The utility of an intraoperative greater trochanteric pain syndrome classification system has now been proven using prospectively collected data, assimilating a decade-long eligibility period following open or endoscopic treatment of peritrochanteric disorders with a minimum two-year follow-up using validated patient-reported outcome scores. This classification guides prognosis and treatment, exactly as an optimal orthopedic classification system should do.The optimal classification system in arthroscopic and related surgery research and clinical practice should be clinically relevant, descriptive, reproducible, simple, inexpensive, safe, and widely applicable. For the hip, classification systems that characterize intra-articular disorders like femoroacetabular impingement (FAI) syndrome, dysplasia, labral tears, and articular cartilage disease predominate the literature. Recently, awareness of peritrochanteric and other extra-articular disorders has increasingly led to greater recognition, diagnosis, and treatment of what has been historically known as "just bursitis". These disorders are far more complex and include greater trochanteric pain syndrome, the spectrum of gluteal tendon pathology, greater trochanteric bursitis, snapping iliotibial band (external coxa saltans), and greater trochanteric-ischial impingement. The utility of an intraoperative greater trochanteric pain syndrome classification system has now been proven using prospectively collected data, assimilating a decade-long eligibility period following open or endoscopic treatment of peritrochanteric disorders with a minimum two-year follow-up using validated patient-reported outcome scores. This classification guides prognosis and treatment, exactly as an optimal orthopedic classification system should do.